Antimicrobial peptides as potential therapeutics for breast cancer. (September 2021) - Aghamiri, Shahin; Zandsalimi, Farshid; Raee, Pourya; Abdollahifar, Mohammad-Amin; Tan, Shing Cheng; Low, Teck Yew; Najafi, Sajad; Ashrafizadeh, Milad; Zarrabi, Ali; Ghanbarian, Hossein; Bandehpour, Mojgan
Abstract: Breast cancer is the most common and deadliest cancer in women worldwide. Although notable advances have been achieved in the treatment of breast cancer, the overall survival rate of metastatic breast cancer patients is still considerably low due to the development of resistance to breast cancer chemotherapeutic agents and the non-optimal specificity of the current generation of cancer medications. Hence, there is a growing interest in the search for alternative therapeutics with novel anticancer mechanisms. Recently, antimicrobial peptides (AMPs) have gained much attention due to their cost-effectiveness, high specificity of action, and robust efficacy. However, there are no clinical data available about their efficacy. This warrants the increasing need for clinical trials to be conducted to assess the efficacy of this new class of drugs. Here, we will focus on the recent progress in the use of AMPs for breast cancer therapy and will highlight their modes of action. Finally, we will discuss the combination of AMP-based therapeutics with other breast cancer therapy strategies, including nanotherapy and chemotherapy, which may provide a potential avenue for overcoming drug resistance. Graphical Abstract: ga1